If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying an + -2 + 7n = 20 Reorder the terms: -2 + an + 7n = 20 Solving -2 + an + 7n = 20 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '2' to each side of the equation. -2 + an + 2 + 7n = 20 + 2 Reorder the terms: -2 + 2 + an + 7n = 20 + 2 Combine like terms: -2 + 2 = 0 0 + an + 7n = 20 + 2 an + 7n = 20 + 2 Combine like terms: 20 + 2 = 22 an + 7n = 22 Add '-7n' to each side of the equation. an + 7n + -7n = 22 + -7n Combine like terms: 7n + -7n = 0 an + 0 = 22 + -7n an = 22 + -7n Divide each side by 'n'. a = 22n-1 + -7 Simplifying a = 22n-1 + -7 Reorder the terms: a = -7 + 22n-1
| 7-2x=5x-14 | | m-3m+4=m+5m-2 | | f(x)=-15x^2+555x+5130 | | y=(x+1)(x-1)(x-3) | | X(a-4b)=5m(x-c)forx | | 1/4=x-2/9 | | 10x-5=9-6x | | C=2*3.14*3 | | 130+4x=234-2.5x | | a-3b=43 | | y-4(2-y)+3y=3(y-4) | | X(a-4b)=5m(x-c) | | 9.375=X/4 | | 3p=4/5 | | (-4x^6d^3)(6x^3d)= | | 6.5x=104 | | n=(n+8)/3 | | 13(x+2)(x+2)-5=22 | | x*2/3+6=-3 | | 16(z-1)(z-1)-29=-28 | | lx+2l=3x | | x*1=1 | | 9(z+1)(z+1)+12=16 | | x=-5+3y | | 7x-4=-46 | | (y+3)(y+3)=4 | | p+26=22 | | -2/3a=6 | | 12(x-11)(x-11)+12=30 | | a^2+b^2-1=0 | | 9d+(8+5.5)=24 | | 81n+33=42 |